Cloning and Characterization of α-S1-casein (CSN1S1) gene and Protein in Indian buffalo (Bubalus bubalis) - Mehra, Vinay K.; Malakar, Dhruba; Kumar, Satish (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
In buffalo, casein genes are located on chromosome 7 (250 kb). The genetic variants of caseins influence the production and nutritional quality of milk. The bovine α s1-casein is up to 40 % of total bovine caseins in milk and is encoded by CSN1S1 gene ( 17.5 kb) and it is identified as allergens and responsible for cow’s milk allergy in infants. CSN1S1 gene was amplified using gene-specific primers, cloned into pJET1.2 cloning vector. The full ORF of buffalo CSN1S1 gene was characterized, which consisted of 801 bp. The protein sequence analysis of buffalo CSN1S1 gene showed that serine is replaced by leucine at 193 amino acid position. The negative GRAVY (grand average of hydropathy) value of αs1-casein protein indicated the hydrophilic nature and high percentage (44.86%) of random coils in confirmed flexible nature of the protein. NetPhos 3.1 analysis showed this protein was phosphorylated (17 residues), which may be involved in post-translational modification processes. IEDB (The Immune Epitope Database) analysis showed 3 potential immunological sites in α s1-casein for B-cell, which may involve certain immunological responses. The phylogenetic tree showed that cattle, yak and buffalo formed one cluster (95%) with a closer relationship between Bos taurus and Bos indicus (99%). The buffalo CSN1S1 gene is closer to yak CSN1S1 gene (95%).